Kenaikan Nafkah Anak Setiap Tahun Pasca Perceraian Perspektif SEMA Nomor 03 Tahun 2015 - Adiningrum, Nuriyah Wulan; Adityo, Rayno Dwi (Morality: Jurnal Ilmu Hukum; Vol 10 No 1 (2024): Morality : Jurnal Ilmu HukumDO - 10.52947/morality.v10i1.343, 2024)
Divorce results in rights and obligations that must be fulfilled by both parents towards their children, one of which is the child's maintenance. Broadly speaking, the applicable law justifies that the fulfillment of child maintenance payments is the obligation of a father to his child. However, the Judge determined that an additional fee of 10% annually in this determination was considered in accordance with SEMA No. 3 of 2015. The type of research used by the author is normative juridical research which functions as a search for truth coherence by adjusting between legal symptoms and statutory regulations and applicable legal norms. The author also uses a research approach in the form of legislation (statute approach) and a case approach (case approach). In this case the authors conducted normative juridical research on the determination of No. 319/Pdt.G/2022/PA.Kdr. The research results of this writing are that in fulfilling the child's living, it must be given proportionally with 2 limitations, namely looking at the father's ability and the child's needs. Based on the outline of the legal language, there are no provisions that specifically regulate the amount of maintenance that must be given, instead there is a clause that the fulfillment of child maintenance must be given proportionally. That is, the legal context only states that the income provided can meet the needs of the child, be it clothing, food, education and health needs. When viewed from the aspect of the father's limitations and abilities contained in the laws and regulations, the Judge is not yet right to apply SEMA No. 3 of 2015 against the decision. Based on the theory of legal grammatical interpretation, in Item 14 of the SEMA Chamber of Religion Section No. 03 of 2015 provides an opportunity for Religious Court Judges to implement it in the form of an optional, so that these provisions are not coercive and do not contain criminal provisions.